Preparation and characterization of Tobacco polysaccharides and its modulation on hyperlipidemia in high-fat-diet-induced mice - Shuaishuai Chang; Xuanhao Lei; Weijia Xu; Feng Guan; Jian Ge; Fuzhao Nian (Scientific Reports)
Abstract This study aimed to investigate the structural properties of tobacco polysaccharide (TP) and its mechanism of modulating hyperlipidemia in high-fat diet-induced mice. The structural properties of TP were characterized by FT-IR, 1HNMR, SEM, AFM and thermogravimetric analysis. And the regulatory mechanism of TP on lipid metabolism was investigated in hyperlipidemia mice. These results showed that TP had a high composition of reducing monosaccharide and the glycosidic bond type was α-glycosidic bond. The intervention by TP resulted in a significant reduction of body weight and improvement in lipid accumulation. And the modulation mechanism by which TP ameliorated the abnormalities of lipid metabolism was associated with the expression levels of lipid metabolism-related genes and serum exosomes miRNA-128-3p, as well as the modulation of structure and abundance of the gut microbiota in mice. In addition, TP treatment significantly increased the content of short-chain fatty acids (SCFAs) in mice feces. The results of molecular docking and dual-luciferase assay exhibited a good interaction between propionic acid and PPAR-α, and it was hypothesized that the interaction might further ameliorate the hyperlipidemia. Therefore, TP can regulate the expression levels of lipid metabolism-related genes through miRNAs from serum exosomes and SCFAs from gut microbiota.